2016
DOI: 10.2754/avb201685010063
|View full text |Cite
|
Sign up to set email alerts
|

The method of preparation and use of vasectomized stallions to regulate the sexual function in mares during hippodrome testing

Abstract: The objective of this study was to develop a method of preparation and use of vasectomized stallions, and to test them as a factor preventing genital functional disorders in mares during training and hippodrome testing. Thoroughbred mares of English, Arabic and Akhal-Teke breeds owned by horse ranches of the Republic of Kazakhstan were used in the research. Vasectomy techniques were mastered on a slaughtering material, and then field tested on stallions. A series of experiments were set for comparative evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It can take from 1 to 2 h between a tick bite and actual infestation of a person with Borrelia. Painful sensations occur only 6-8 h after the tick bite, while it usually takes several days for the female tick to saturate with blood [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It can take from 1 to 2 h between a tick bite and actual infestation of a person with Borrelia. Painful sensations occur only 6-8 h after the tick bite, while it usually takes several days for the female tick to saturate with blood [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…This was due to in week 3 the ejaculation had sperm in both techniques while the spermatozoa disappeared at week 4 post-operation. In fact, numerous authors such as Julanova et al , [11] Barone et al , [15] Sokal et al , [16] Cook et al , [18] Ibrahiem [20] demonstrated different techniques to create vasectomized patients. In the present study, the reproductive efficient examination of both techniques did not establish the significant differences between the EL and AL techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These methods depend on males have the ability to mate the female without ejaculation. Vasectomized males are modified surgically so retain natural sexual desire may occur, but this method is occlusion of the sperms’ passage [11]. The first and oldest method was excision-ligation (EL) of vas deferens [12].…”
Section: Introductionmentioning
confidence: 99%